2003
DOI: 10.1002/qaj.228
|View full text |Cite
|
Sign up to set email alerts
|

History of FDA good laboratory practices

Abstract: The United States Food and Drug Administration (FDA) requires nonclinical studies of new drugs, food additives and chemicals to predict their safety and potential efficacy in humans. The significance of the information gained from these studies requires that they be conducted according to sound scientific principles and with strict attention to quality assurance and quality control. Human health and safety are dependent upon the decisions made from these studies. The discovery of the lack of companies' adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…GLP is a quality system concerned with the organizational process and the conditions, under which non-clinical health and environmental safety studies are planned, performed, monitored, recorded, archived, and reported [17].…”
Section: Methodology and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…GLP is a quality system concerned with the organizational process and the conditions, under which non-clinical health and environmental safety studies are planned, performed, monitored, recorded, archived, and reported [17].…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…The positions defined in the GLP guideline are: test facility management, test site management, sponsor, study director, principal investigator, study personnel, and archivist [17]. To this end, an organizational structure was defined by aligning the existing responsibilities of platform personnel with the positions created by GLP implementation.…”
Section: Organization and Definition Of Glp Positionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This decision prompted the development of international guidelines and the implementation of Good Laboratory Practices (Baldeshwiler, 2003).…”
Section: Concept Articlementioning
confidence: 99%
“…The Good Laboratories Practice (GLP) regulation (21CFR Part 58) was codified in 1978 in response to poor practices by a few laboratories involved in the conduct of preclinical safety studies (Baldeshwiler, 2003). Since that time, many regions have developed GLP regulations.…”
Section: Nonclinical Drug Development and The Fdamentioning
confidence: 99%